Greater or Reduced Economic Freedom? Consequences Following From Contemporary Economic Crisis - Jarecki, Wojciech (Oeconomia Copernicana, 2014)
The paper is aimed at stating if economic crisis observed during the period 2007-2009 will give rise to greater or reduced economic freedom. Seeking the answer to this question, Economic Freedom Index developed by Fraser Institute during the period 2007-2010 was subject to analysis. The research covered the European Union and the United States of America.